2017
DOI: 10.1097/jom.0000000000001084
|View full text |Cite
|
Sign up to set email alerts
|

Linking Compensation and Health Surveillance Data Sets to Improve Knowledge of US Coal Miners’ Health

Abstract: Objective Increase knowledge of US coal miners’ respiratory health by linking data from the black lung benefits program (BLBP) and the coal workers’ health surveillance program (CWHSP). Methods BLBP claims data from 2000 through 2013 was linked to CWHSP data from 1970 through 2016. Results Overall, 273,644 miners participated in CWHSP, 37,548 in BLBP, and 22,903 in both programs. Median age of miners at their time of first/only participation in CWHSP was 28 and 32 years, respectively. BLBP claimants were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…This is an observation that has been borne out from analyses of federal disability compensation data where 39% of miners with disabling pneumoconiosis did not participate in the NIOSH CWHSP during their working careers. 41 While the collective approach to assessing and protecting the respiratory health of the US coal mining workforce can certainly be improved, continued monitoring of respiratory health of actively working coal miners is necessary for early intervention to avoid unnecessary progression to the most advanced stages of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an observation that has been borne out from analyses of federal disability compensation data where 39% of miners with disabling pneumoconiosis did not participate in the NIOSH CWHSP during their working careers. 41 While the collective approach to assessing and protecting the respiratory health of the US coal mining workforce can certainly be improved, continued monitoring of respiratory health of actively working coal miners is necessary for early intervention to avoid unnecessary progression to the most advanced stages of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that these findings also demonstrate that pneumoconiosis continues to occur among contemporary coal miners in the United States despite it being clear that this system has not identified every case of pneumoconiosis among currently employed coal miners. This is an observation that has been borne out from analyses of federal disability compensation data where 39% of miners with disabling pneumoconiosis did not participate in the NIOSH CWHSP during their working careers 41 . While the collective approach to assessing and protecting the respiratory health of the US coal mining workforce can certainly be improved, continued monitoring of respiratory health of actively working coal miners is necessary for early intervention to avoid unnecessary progression to the most advanced stages of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, these forms of secondary prevention of CWP are underutilised. A recent study showed that 39% of miners who first applied for federal black lung benefits during 2000–2016 had never participated in the CWHSP during their career 15. Among miners who did participate in the CWHSP during 1986–2016 and were found to be eligible for transfer rights, only 14.4% chose to exercise their transfer right 16.…”
Section: Discussionmentioning
confidence: 99%
“…[45] Among miners applying for benefits through BLBP since the year 2000, 39% did not participate in CWHSP screening while they were employed. [46] Pneumoconiosis caused by coal mine dust is a progressive disease and respiratory morbidity including ongoing fibrosis and functional impairment can occur after exposure ceases. To our knowledge, no contemporary studies have explicitly focused on post-exposure progression in the USA.…”
Section: Pneumoconiosis In Former Coal Minersmentioning
confidence: 99%